Effects of comorbidity burden and age on brain integrity in HIV. (1st June 2019) - Saloner, Rowan; Heaton, Robert K.; Campbell, Laura M.; Chen, Anna; Franklin, Donald; Ellis, Ronald J.; Collier, Ann C.; Marra, Christina; Clifford, David B.; Gelman, Benjamin; Sacktor, Ned; Morgello, Susan; et al.
Abstract : Objective: The influence of confounding neurocognitive comorbidities in people living with HIV (PLWH) on neuroimaging has not been systematically evaluated. We determined associations between comorbidity burden and brain integrity and examined the moderating effect of age on these relationships. Design: Observational, cross-sectional substudy of the CNS HIV Antiretroviral Therapy Effects Research cohort. Methods: A total of 288 PLWH (mean age = 44.2) underwent structural MRI and magnetic resonance spectroscopy as well as neurocognitive and neuromedical assessments. Consistent with Frascati criteria for HIV-associated neurocognitive disorders (HAND), neuromedical and neuropsychiatric comorbidity burden was classified as incidental (mild), contributing (moderate), or confounding (severe-exclusionary) to a diagnosis of HAND. Multiple regression modeling predicted neuroimaging outcomes as a function of comorbidity classification, age, and their interaction. Results: Comorbidity classifications were 176 incidental, 77 contributing, and 35 confounded; groups did not differ in HIV disease characteristics. Relative to incidental and contributing participants, confounded participants had less cortical gray matter and more abnormal white matter and ventricular cerebrospinal fluid, alongside more neuroinflammation (choline, myo-inositol) and less neuronal integrity ( N -acetylaspartate). Older age exacerbated the impact of comorbidity burden: to a greater extent in the confounded group, older age was associated with more abnormal white matter ( P = 0.017), less total white matter ( P = 0.015), and less subcortical gray matter ( P = 0.014). Conclusion: Neuroimaging in PLWH reveals signatures associated with confounding neurocognitive conditions, emphasizing the importance of evaluating these among individuals with suspected HAND. Older age amplifies subcortical and white matter tissue injury, especially in PLWH with severe comorbidity burden, warranting increased attention to this population as it ages.